Team-based Introductory Research Experiences in Mathematics. Issue 3 (16th March 2017) - Baum, Brittany Smith; Rowell, Ginger Holmes; Green, Lisa; Yantz, Jennifer; Beck, Jesse; Cheatham, Thomas; Stephens, D. Christopher; Nelson, Donald
Abstract: As part of Middle Tennessee State University's (MTSU's) initiative to improve retention of at-risk STEM majors, they recruit first-time, full-time freshman STEM majors with mathematics ACT scores of 19 to 23 to participate in MTSU's "Mathematics as a FirstSTEP to Success in STEM" project (FirstSTEP). This article overviews MTSU's FirstSTEP research approach and demonstrates that introductory, early research experiences can be successful for mathematics projects. At the end of their freshman year, mathematics students can develop a foundation to conduct mathematical research, increase depth of content knowledge, and build confidence in their technical abilities.